Minimally invasive posterior cervical microforaminotomy in the lower cervical spine and C-T junction assisted by O-arm-based navigation. (May 2013) - Curto, David Del; Kim, Jin-Sung; Lee, Sang-Ho
<x xml:space="preserve">Abstract</x> Navigated posterior cervical microforaminotomy (PCM) is a promising minimally invasive technique for treating radiculopathy caused by lateral disc herniations and foraminal stenosis. Between December 2009 and October 2010, 14 patients with unilateral foraminal disc herniations or foraminal stenosis at the C6-7 or C7-T1 level underwent PCM assisted by O-arm navigation using the METRx tubular retractor. The main symptoms were radicular arm pain with no significant neck pain. Successful relief of radicular pain was achieved in all 14 patients. Two of the patients were lost during follow-up, and three had to undergo further decompression due to remnant foraminal stenosis being discovered on intraoperative O-arm images. There were no cases of instability or recurrence, and the only complication observed was a dural tear in one patient, which was adequately treated with fibrin glue and bed rest. The duration of symptoms was 4.5 months on average. The mean operation time was 136 minutes, with the additional time required for the image guided surgery assisted by O-arm-based navigation being approximately 28 minutes on average. There were no other complications during the surgical procedure or in the immediate postoperative period. Posterior cervical microforaminotomy assisted by O-arm-based navigation is a safe, effective and minimally invasive procedure for the treatment of lateral disc herniations and foraminal stenosis of the lower cervical spine and C-T junction, offering the possibility of an accurate decompression with a reduced risk of segmental instability.